ANALISIS KETEPATAN PREDIKSI KEBANGKRUTAN:STUDI BANDING MENGGUNAKAN PENDEKATAN BERBASIS AKRUAL DAN ALIRAN KAS (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2012) - Wijayanti, Andri; Marsono, Marsono (Diponegoro Journal of Accounting, 2014)
This study aims to examine the ability of bankruptcy prediction model based on the accrual and cash flow in the financial condition of the predict the onset of distress in the future. The accrual-based bankruptcy prediction models formed of 5 financial ratio's Altman: working capital:total assets retained earnings:total assets, earnings before interest and taxes; total assets, market value of equity:book value of total debt,and sales:total assets. Model prediction bankruptcy based cash flow formed of 3 ratio financial gilbert, belonging to menon, and Schwartz : cash flow opererations:current liabilities, cash flow from operations:total assets, and cash flow from operations:total liabilities.This research using samples of manufacturing companies were listed on the Indonesia Stock Exchange in the period 2009-2012. Financial reporting data in 2009, 2010 and 2011 is used to predict the onset of conditions of financial distress in the coming year , which is the year 2010, 2011. and 2012. This research uses statistical tools to form the discriminant analysis model predictions of bankruptcy.The results showed that the accrual-based bankruptcy prediction models have the same predictive capabilities as model predictions of cash flow-based bankruptcy. It is shown with the result of two sample propotion test which show Z value < t table. Both of based bankruptcy prediction models and cash flow-based bankruptcy prediction models can classifies companies into the group of non financial distress and financial distress with the same capabilities.Â